Waste heat recovery from high-temperature solid granular materials: Energy challenges and opportunities. (December 2019) - Cheng, Zhilong; Guo, Zhigang; Tan, Zhoutuo; Yang, Jian; Wang, Qiuwang
Abstract: Large amounts of high-temperature solid granular (HTSG) materials, for example iron-ore sinters, cement, coke and slags are produced throughout the world in metallurgy and building materials industries, where as 4.29 billion tons in China, 0.49 billion tons in India and 0.24 billion tons in United States per annum. Those activities are very energy intensive, and therefore the implementation of waste heat recovery technologies would have great potential to make contributions to the reductions of primary energy consumption and greenhouse gas emission in the longer term. In the community of HTSG waste heat recovery in metallurgy and building materials industries, there are two critical features: wide partice size range and wide temperature range. This work aims at reviewing progress on the key fundamental nature, advanced technologies and future issues in waste heat recovery from HTSG materials. The configurations and limitations of current waste heat recovery techniques depending on solid particle size are addressed. In particular, a new waste heat recovery device for solid particles consisting of powder and lump materials is discussed. Additionally, the available multi temperature stages heat recovery techniques, combined usage of different heat recovery manners, and development of compact heat exchangers are critiqued. The available techniques to minimize the negative impacts of HTSG property variations during rapid temperature change are introduced. The key findings of this review provide avenues to promote the development of novel waste heat recovery technologies which is helpful to improve energy efficiency and reduce greenhouse gas emission. Highlights: Two critical features of solid granular in metallurgy and building materials industries are presented. Configurations and limitations of available techniques based on key features of solid granular are addressed. Fundamental nature, advanced technologies and future issues of solid granular heat recovery are summarized.